Edukasi Gampong Berbasis Kewirausahaan dan Inovasi Ekonomi Lokal di Meunasah Leubok Aceh Utara - Akhyar, Juni; Harliyana, Iba; Wulanda, Wulanda (Jurnal Solusi Masyarakat (JSM), 2024)
Gampong Mns Leubok AB, Lhoksukon District, North Aceh Regency is a Gampong that has a population of approximately 500 people, with the majority of their livelihood being farmers. Gampong Mns Leubok AB also has various potential natural resources that are quite potential to be developed, namely fish cultivation, where Gampong Leubok is located almost on the coast. Gampong Mns Leubok AB also has the potential to develop agricultural businesses such as fertilizer and agricultural plant medicine businesses, because most of the people in Leubok gampong also make their living by farming rice crops. Gampong Mns Leubok AB also has the potential to develop agricultural technology development efforts. Entrepreneurship-based Gampong Education: Innovation to Build the Local Economy Entrepreneurship-based Gampong Education: Innovation to Build the Local Economy in Gampong Mns Leubok AB, Lhoksukon sub-district, North Aceh Regency, was implemented to provide entrepreneurship knowledge to the community to be able to encourage the community to form business groups based on village potential. So that it can expand employment opportunities and encourage the community's economy and have an impact on the welfare of the local community, especially the community of Gampong Mns Leubok AB, Lhoksukon District, North Aceh Regency